Development of Social Studies E-Module Based on Culturally Responsive Teaching Containing Local Wisdom Ngalaksa Baliung: A Study Of Validity, Practicality, and Effectiveness in Improving The Collaboration Ability of Elementary School Students - Uu Ubadulloh; Eka Nurhidayat; Yuyun Dwi Haryanti; Devi Ariyuni Yonanda (Eduvest - Journal of Universal Studies, 2026)
This research aimed to develop a Social Studies e-module based on Culturally Responsive Teaching incorporating the local wisdom of Ngalaksa Baliung to improve elementary school students’ collaboration skills. The study employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The research subjects consisted of subject matter experts, media experts, teachers, and elementary school students. Data were collected through validation questionnaires, practicality questionnaires, collaboration skill tests, and observations. Data analysis techniques included Aiken’s V, Cronbach’s alpha, and the N-gain index. The results showed that the developed e-module had a high level of validity in terms of content, construct, and instructional design. The product also demonstrated a high level of practicality based on teacher and student responses and was effective in improving students’ collaboration skills, with improvements in the medium to high category. The integration of local wisdom values and culture-based learning approaches was proven to enhance students’ social engagement and interaction. This study contributes to the development of culturally based digital teaching materials that support the implementation of deep learning within the Independent Curriculum and strengthen elementary students’ collaborative character.